The Learners’ Motivation to Speak English Through Role-Playing Games - Paschalis Kurniawan Sanjaya; Fidelis Chosa Kastuhandani (Universitas Muhammadiyah Barru, 2025)
This research aimed to explore the role of Role-Playing Games in students' speaking motivation and how they maintain it. It is because in this era, video games, particularly Role-Playing Games (RPGS), have gained significant popularity among young generation. Recently, even in the academic field, video games' effect on motivation to learn English has received considerable attention among researchers. However, motivation in speaking English through role-playing video games, particularly focusing on college students, remains an underexplored area of research. Therefore, the researcher decided to conduct research on “Learners' motivation to speak English Through Role-Playing Games.” Two research questions were raised: 1) How do Role-Playing Games (RPGs) motivate learners to speak English? 2) How to maintain a learner's motivation to speak English when playing Role-Playing Games (RPGs)? Guided by Self-Determination Theory by Edward L. Deci and Richard Ryan, this research employed descriptive qualitative methods. The research participants were English Language Education Study Program (ELESP) students of Sanata Dharma University, who were carefully selected using purposive sampling. The data was collected using in-depth interviews with five interviewees. The researcher analyzed the data using thematic analysis, which includes transcription, coding, and interpretation of the collected data. The result showed that role-playing games can motivate learners to speak through interaction between players, the existence of goals, and positive feedback from peers. Furthermore, staying curious and remembering the goal can maintain learners' motivation to always speak English when playing games. This research offered valuable insights for learners and educators which might be useful for future education.